Analisis Kelayakan Tanah Dasar Sebagai Subgrade Jalan Ditinjau Dari Kualitas Daya Dukung Tanah (Studi Kasus Ruas Jalan Anggrek Kota Kupang): Analysis Of Damage To Road Pavement From The Quality Of Soil Bearing Capacity (Case Study Of Anggrek Street Kupang City) - Daud, Deasi D. A. A.; Tuati, Anie A.; Hayer, Yacob V. (Media Ilmiah Teknik Sipil, 2024)
An area’s function changes as a result of development, which is followed by an increase in vehicle traffic but not enough road capacity. This causes the road to break down quickly because the carrying capacity of the soil isn’t strong enough to handle the volume of vehicles crossing it. The road construction will quickly suffer damage if the subgrade has a low carrying capacity. The current damage to the Anggrek road makes driving uncomfortable from a visual perspective. The road section was damaged, according to field observations, with crocodile skin cracks, longitudinal cracks, subsidence, furrows, and potholes. Based on laboratory tests, the purpose of this study was to examine the damage to the Anggrek road caused by the quality of the soil’s carrying capacity. The quantitative analysis and interpretation of the soil test result data is the research method. The analysis reveals that the subgrade soil on the Anggrek road in Kupang City is of the fine-grained organic clay type and has moderate to high plasticity. It is also easily influenced by water and the season or weather, so the water content can easily rise or fall. It is also easy to change the volume of soil content depending on the water content. The CBR value of the soil is low, and it does not meet the requirements outlined in the BM Specifications 2018 Rev 2 of 2020. The assessment